Analytical isoelectric focusing of R factor-determined beta-lactamases: correlation with plasmid compatibility. - Matthew, M (1976)
R factor-determined beta-lactamases have been investigated by analytical isoelectric focusing. The enzymes such as those specified by the R6K and RP4 plasmids (TEM-type enzymes) are notably homogenous in biochemical tests (Hedges et al., 1974), but two subclasses can be distinguished by isoelectric focusing. Three subclasses can be distinguished among the oxacillin-hydrolyzing enzymes, in good agreement with the classification based upon biochemical characteristics (Dale and Smith, 1974). The TEM-type beta-lactamases are promiscuously distributed among plasmids of a wide variety of compatibility groups, whereas the various oxacillin-hydrolyzing enzymes show some degree of correlation with compatibility.